Preparation method of antibacterial corrosion-resistant micro-arc oxidation film layer on surface of aluminum alloy

The microarc oxidation process forms an antibacterial corrosion-resistant film layer on the surface of the aluminum alloy, which solves the problems of the permeability and insufficient antibacterial performance of aluminum alloys, and achieves widespread application in the medical field.

CN119571408APending Publication Date: 2025-03-07DALIAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411552593.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Aluminum alloys are prone to corrosion and have insufficient antibacterial properties, which limits their application in the medical field.

Method used

The microarc oxidation process is used to form an antibacterial and corrosion-resistant film layer on the surface of the aluminum alloy. By adding nanoCuO particles to the electrolyte, the antibacterial and corrosion-resistant film layer is improved.

Benefits of technology

The excellent antibacterial rate (80.66%-99.99%) and corrosion resistance of aluminum alloy materials are achieved, reducing the dependence on antibiotics and reducing the risk of allergic reactions to the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005115470480000011
    Figure HDA0005115470480000011
  • Figure HDA0005115470480000012
    Figure HDA0005115470480000012
  • Figure HDA0005115470480000021
    Figure HDA0005115470480000021
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum alloy surface treatment, in particular to a preparation method of an antibacterial and corrosion-resistant micro-arc oxidation film layer on the surface of an aluminum alloy. According to the method, a film layer is formed on the aluminum alloy surface through micro-arc oxidation; the micro-arc oxidation electrolyte comprises water, alkaline hydroxide, silicate and nano CuO particles; in the electrolyte, the mass concentration of the alkaline hydroxide is 1g / L-15g / L, the mass concentration of the silicate is 1g / L-25g / L, and the mass concentration of the nano CuO particles is 0.1 g / L-20g / L; the method comprises the following steps: by taking an aluminum alloy workpiece as an anode and a stainless steel container as a cathode, treating for 2-30 minutes at the temperature of 20-85 DEG C under the conditions that the positive voltage is 200V-700V, the negative voltage is 50V-150V, the pulse width is 200ms-4000ms, the pulse interval is 200ms-1000ms and the treatment time is 2-30 minutes. The nano CuO particles are introduced to obtain the micro-arc oxidation film layer with antibacterial and anti-corrosion functions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum alloy surface treatment, and in particular to a method for preparing an antibacterial and corrosion-resistant micro-arc oxidation film layer on the surface of an aluminum alloy. Background Art

[0002] Bacterial infections during surgery pose a significant risk to patient health, often leading to serious complications or even death. According to the World Health Organization (WHO), more than 300 million surgical operations are performed worldwide each year, with an incidence of healthcare-associated infections of 0.14% (increasing by 0.06% per year), which can lead to prolonged hospital stays, long-term disability, increased antimicrobial resistance, and increased economic burdens on patients, families, and health systems. The most common pathogens include Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. Due to the overuse and abuse of antibiotics, multidrug-resistant "superbugs" have become a global public health problem. In clinical settings, traditional disinfection methods and antibiotics are effective, but their effectiveness gradually weakens as bacteria become more adaptable. Therefore, there is an urgent need to find alternative solutions to reduce the use of antibiotics and control bacterial resistance.

[0003] The development of antibacterial materials has become an important direction in biomedical research today. Aluminum and its alloys are widely used in medical devices due to their excellent mechanical properties and lightweight characteristics. However, aluminum alloys are susceptible to corrosion and have insufficient antibacterial properties, which limits their application in the medical field. In addition, aluminum ions may cause allergic reactions in human tissues, and this deficiency needs to be overcome by improving their corrosion resistance. Therefore, the development of an aluminum alloy matrix material with excellent antibacterial and corrosion resistance is of great significance for expanding its application in the medical field. Summary of the invention

[0004] The purpose of the present invention is to solve the problem that aluminum alloy is easy to corrode and has insufficient antibacterial performance. A method for preparing a micro-arc oxidation antibacterial and corrosion-resistant film layer on the surface of an aluminum alloy is proposed. The prepared aluminum alloy material has an antibacterial rate of 80.66%-99.99% (Staphylococcus aureus), a corrosion voltage of 0V-+0.697V, and a corrosion current density of 1.89×10 -7 Acm -2 -9.51×10 -7 Acm -2 .

[0005] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:

[0006] The invention provides a method for preparing an antibacterial and corrosion-resistant micro-arc oxidation film layer on the surface of an aluminum alloy. The method comprises treating an aluminum alloy workpiece with micro-arc oxidation to form a film layer on the surface of the aluminum alloy. The electrolyte of the micro-arc oxidation comprises water, alkaline hydroxide, silicate and nano CuO particles. In the electrolyte, the mass concentration of the alkaline hydroxide is 1g / L-15g / L, the mass concentration of the silicate is 1g / L-25g / L, and the mass concentration of the nano CuO particles is 0.1g / L-20g / L. The micro-arc oxidation uses the aluminum alloy workpiece as an anode and a stainless steel container as a cathode, uses a pulsed AC power supply for treatment, and has a forward voltage of 200V-700V, a negative voltage of 50-150V, a pulse width of 200ms-4000ms, an interval between pulses of 200ms-1000ms, a temperature of 20°C-85°C, and a treatment time of 2min-30min.

[0007] In the above technical solution, further, the forward voltage is: 400V-600V, the negative voltage is: 70V-120V, the pulse width is: 1000ms-3000ms, and the pulse interval is: 250ms-750ms; the hydroxide concentration is 1-3g / L, the silicate concentration is 2-5g / L, and the nano-CuO particle concentration is 8-15g / L.

[0008] In the above technical solution, further, the pH value of the electrolyte is 8-14.

[0009] In the above technical solution, further, the alkaline hydroxide includes one or more of potassium hydroxide and sodium hydroxide; the silicate includes one or more of sodium silicate and potassium silicate; the diameter of the nano copper oxide particles is 1nm-100nm, and the preferred diameter of the nano copper oxide particles is 40nm-60nm.

[0010] In the above technical solution, further, the electrolyte is stirred to form a colloid in which nano-CuO particles are evenly dispersed before micro-arc oxidation.

[0011] In the above technical solution, further, the power supply is a bipolar pulse power supply, which adopts a unidirectional mode or a unidirectional first and then bidirectional working mode.

[0012] In the above technical solution, further, the aluminum alloy is 2024 aluminum alloy, 7075 aluminum alloy or 6061 aluminum alloy.

[0013] In the above technical solution, further, the aluminum alloy workpiece is polished, cleaned, and dried before micro-arc oxidation treatment, and is specifically polished with 2000-mesh metallographic sandpaper. After polishing, the substrate is cleaned with deionized water and dried at room temperature.

[0014] The present invention also provides an antibacterial and corrosion-resistant micro-arc oxidation film layer on the surface of an aluminum alloy, which is prepared by the above-mentioned preparation method.

[0015] The present invention also provides the application of the aforementioned antibacterial and corrosion-resistant micro-arc oxidation film layer on the surface of the aluminum alloy in microsurgical instrument materials, orthopedic external fixator materials, and thoracic surgical instrument materials.

[0016] The beneficial effects of the present invention are:

[0017] The present invention adopts micro-arc oxidation process to prepare aluminum alloy surface film layer, and adds copper oxide nanoparticles in the working solution. The prepared film layer improves the antibacterial and corrosion resistance of aluminum alloy material at the same time, and the antibacterial rate reaches 80.66%-99.99% (Staphylococcus aureus), the corrosion voltage reaches 0V-+0.697V, and the corrosion current reaches 1.89×10 -7 Acm -2 -9.51×10 -7 Acm -2 , all have good antibacterial and corrosion resistance, and copper is evenly distributed in the coating and stably embedded. Compared with stainless steel, aluminum alloy has a larger specific stiffness, the same mechanical properties, and a lighter weight; compared with titanium alloy, it has the economic advantage of low price. The stable and good corrosion resistance of the film layer of the present invention makes it difficult for the aluminum alloy to cause an allergic reaction in the human body due to release when it comes into contact with body fluids. Its excellent antibacterial properties make it possible to use it as a medical device material. This makes it possible for my country's abundant reserves of aluminum to be used on a large scale in the medical industry.

[0018] The micro-arc oxidation process of the present invention has a simple working fluid formula and fewer overall processes. The micro-arc discharge treatment time is generally 2 minutes to 40 minutes. Since the micro-arc oxidation treatment time is short and the discharge only occurs on the surface of the workpiece, the temperature of the workpiece substrate does not change much before and after the micro-arc oxidation treatment, and will not deform due to thermal stress. It is worth pointing out that the micro-arc oxidation technology uses an alkaline working fluid with a low concentration, which is more environmentally friendly than the acidic and high-concentration working fluid of anodizing. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Preparation of antibacterial and corrosion-resistant film and flow chart of antibacterial testing;

[0020] Figure 2 Antibacterial detection diagram of the antibacterial and corrosion-resistant film layer of Example 5;

[0021] Figure 3 Polarization curve diagram of the antibacterial and corrosion-resistant film layer of Example 5;

[0022] Figure 4 Cross-sectional morphology of the film layer of Example 5;

[0023] Figure 5 EDS image of Cu film layer in Example 5. DETAILED DESCRIPTION

[0024] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.

[0025] The present invention is described in detail below by specific examples, but the protection scope of the present invention is not limited. Unless otherwise specified, the experimental methods used in the present invention are conventional methods, and the experimental equipment, materials, reagents, etc. used can be obtained from commercial channels; the diameter of the nano copper oxide particles used is 40nm-60nm.

[0026] Example 1

[0027] A preparation method of a micro-arc oxidation antibacterial and corrosion-resistant film layer on the surface of a 2024 aluminum alloy is carried out according to the following steps:

[0028] The polished and cleaned aluminum alloy sheet was used as the anode, and the 316 stainless steel container was used as the cathode. A pulsed AC power supply was used to perform micro-arc oxidation treatment in a unidirectional and then bidirectional manner. The anode of the aluminum alloy workpiece was immersed in the working liquid, and then bipolar pulse electricity was applied to both the cathode and the anode, with a forward voltage of 700V, a negative voltage of 80V, a pulse width of 4000ms, and an interval of 500. Under the condition of a temperature below 85°C, the antibacterial and corrosion-resistant film layer of micro-arc oxidation on the surface of the aluminum alloy was obtained after 20 minutes of treatment.

[0029] The working solution is a mixture of deionized water, alkaline hydroxide, silicate and nano copper oxide particles; the concentration of sodium hydroxide in the working solution is 1 g / L, the concentration of sodium silicate is 8 g / L and the concentration of nano copper oxide is 20 g / L.

[0030] The aluminum alloy is 2024 aluminum alloy, and the size is 20 mm×20 mm×2 mm.

[0031] Before the micro-arc oxidation treatment, the electrolyte was stirred for 30 minutes by a magnetic stirring pump at a speed of 1500 rad / min to ensure that the nano-CuO particles were evenly dispersed to form a stable colloid.

[0032] The initial water temperature in this embodiment is 20°C.

[0033] The antibacterial rate of the micro-arc oxidation antibacterial and corrosion-resistant film prepared in this embodiment is 99.06% (Staphylococcus aureus), the corrosion voltage is +0.269V, and the corrosion current is 3.51×10 -7 The film thickness is 50μm to 60μm.

[0034] Example 2

[0035] A micro-arc oxidation antibacterial and corrosion-resistant film layer on the surface of a 7075 aluminum alloy is prepared by the following steps:

[0036] The polished and cleaned aluminum alloy sheet was used as the anode, and the 316 stainless steel container was used as the cathode. A pulsed AC power supply was used to perform micro-arc oxidation treatment in a unidirectional and then bidirectional manner. The anode of the aluminum alloy workpiece was immersed in the working liquid, and then bipolar pulse electricity was applied on both sides of the cathode and the anode, with a forward voltage of 500V, a negative voltage of 150V, a pulse width of 2000ms, and an interval of 200. Under the condition of a temperature below 85°C, the antibacterial and corrosion-resistant film layer of micro-arc oxidation on the surface of the aluminum alloy was obtained after 20 minutes of treatment.

[0037] The working solution is a mixture of deionized water, potassium hydroxide, sodium silicate and nano copper oxide particles; the working solution has a concentration of 2 g / L of alkaline potassium hydroxide, 25 g / L of potassium silicate and 0.1 g / L of nano copper oxide.

[0038] The aluminum alloy is 7075 aluminum alloy, and the size is 20 mm×40 mm×2 mm.

[0039] Before the micro-arc oxidation treatment, the electrolyte was stirred for 30 minutes by a magnetic stirring pump at a speed of 1500 rad / min to ensure that the nano-CuO particles were evenly dispersed to form a stable colloid.

[0040] The initial water temperature in this embodiment is 20°C.

[0041] The antibacterial rate of the micro-arc oxidation antibacterial and corrosion-resistant film prepared in this embodiment is 80.66% (Staphylococcus aureus), the corrosion voltage is +0.495V, and the corrosion current is 2.53×10 -7 The film thickness is 50μm to 70μm.

[0042] Example 3

[0043] The preparation of a micro-arc oxidation antibacterial and corrosion-resistant film layer on the surface of a 2024 aluminum alloy is carried out according to the following steps:

[0044] The polished and cleaned aluminum alloy sheet is used as the anode, and the 316 stainless steel container is used as the cathode. A pulsed AC power supply is used to perform micro-arc oxidation treatment in a unidirectional and then bidirectional manner. The anode of the aluminum alloy workpiece is immersed in the working liquid, and then bipolar pulse electricity is applied to both the cathode and the anode. The forward voltage is 200V, the negative voltage is 80V, the pulse width is 200ms, and the pulse interval is 500ms. The treatment is carried out for 30 minutes at a temperature above 20°C. The antibacterial and corrosion-resistant film layer of micro-arc oxidation on the surface of the aluminum alloy is obtained.

[0045] The working solution is a mixture of deionized water, alkaline hydroxide, silicate and nano copper oxide particles; the concentration of sodium hydroxide in the working solution is 2 g / L, the concentration of potassium silicate is 1 g / L and the concentration of nano copper oxide is 6 g / L.

[0046] The aluminum alloy is 2024 aluminum alloy, and the size is 20 mm×20 mm×2 mm.

[0047] Before the micro-arc oxidation treatment, the electrolyte was stirred for 30 minutes by a magnetic stirring pump at a speed of 1500 rad / min to ensure that the nano-CuO particles were evenly dispersed to form a stable colloid.

[0048] The initial water temperature in this embodiment is 20°C.

[0049] The antibacterial rate of the micro-arc oxidation antibacterial and corrosion-resistant film prepared in this embodiment is 97.45% (Staphylococcus aureus), the corrosion voltage is +0.296V, and the corrosion current is 6.81×10 -7 The film thickness is 20μm to 30μm.

[0050] Example 4

[0051] The preparation of a micro-arc oxidation antibacterial and corrosion-resistant film layer on the surface of a 6061 aluminum alloy is carried out according to the following steps:

[0052] The polished and cleaned aluminum alloy sheet is used as the anode, and the 316 stainless steel container is used as the cathode. A pulsed AC power supply is used to perform micro-arc oxidation treatment in a unidirectional and then bidirectional manner. The anode of the aluminum alloy workpiece is immersed in the working liquid, and then bipolar pulse electricity is applied on both sides of the cathode and the anode. The forward voltage is 560V, the negative voltage is 50V, the pulse width is 400ms, and the pulse interval is 1000ms. The temperature is higher than 20°C and the treatment is carried out for 2 minutes. The micro-arc oxidation antibacterial and corrosion-resistant film layer on the surface of the aluminum alloy is obtained.

[0053] The working solution is a mixture of deionized water, alkaline hydroxide, silicate and nano copper oxide particles; the working solution has a potassium hydroxide concentration of 15 g / L, a sodium silicate concentration of 8 g / L and a nano copper oxide concentration of 8 g / L.

[0054] The aluminum alloy is 6061 aluminum alloy, and the size is 20 mm×20 mm×2 mm.

[0055] Before the micro-arc oxidation treatment, the electrolyte was stirred for 30 minutes by a magnetic stirring pump at a speed of 1500 rad / min to ensure that the nano-CuO particles were evenly dispersed and formed a stable colloid with a negative Zeta potential.

[0056] The initial water temperature in this embodiment is 20°C.

[0057] The antibacterial rate of the micro-arc oxidation antibacterial and corrosion-resistant film prepared in this embodiment is 96.67% (Staphylococcus aureus), the corrosion voltage is +0.195V, and the corrosion current is 8.84×10 -7 The film thickness is 10μm to 20μm.

[0058] Example 5

[0059] A preparation method of an antibacterial and corrosion-resistant film layer of micro-arc oxidation on an aluminum alloy surface is carried out according to the following steps:

[0060] The polished and cleaned aluminum alloy sheet is used as the anode and the stainless steel container is used as the cathode. A pulsed AC power supply is used to perform micro-arc oxygen treatment in a unidirectional and then bidirectional manner. The anode of the aluminum alloy workpiece is immersed in the working liquid, and then bipolar pulse electricity is applied to both the cathode and the anode. The forward voltage is 600V, the negative voltage is 120V, the pulse width is 2000ms, and the pulse interval is 1000ms. The treatment is carried out for 20 minutes at a temperature above 20°C. The micro-arc oxidation antibacterial and corrosion-resistant film layer on the surface of the aluminum alloy is obtained.

[0061] The working solution is a mixture of deionized water, alkaline hydroxide, silicate and nano copper oxide particles; the concentration of sodium hydroxide in the working solution is 3g / L, the concentration of sodium silicate is 8g / L and the concentration of nano copper oxide is 8g / L.

[0062] The aluminum alloy is 2024 aluminum alloy, and the size is 20 mm×20 mm×2 mm.

[0063] Before the micro-arc oxygen treatment, the electrolyte was stirred for 30 minutes by a magnetic stirring pump at a speed of 1500 rad / min to ensure that the nano-CuO particles were evenly dispersed to form a colloid.

[0064] The initial water temperature in this embodiment is 20°C.

[0065] The micro-arc oxidation antibacterial and corrosion-resistant film layer prepared in this embodiment has copper element effectively and evenly incorporated into the film layer. Figure 5 shown.

[0066] The antibacterial rate of the micro-arc oxidation antibacterial and corrosion-resistant film prepared in this embodiment is 98.83% (Staphylococcus aureus). Figure 2 As shown. The corrosion voltage is +0.186V and the corrosion current is 2.21×10 -7 ,like Figure 3 The film thickness is 40μm to 50μm, as measured by an eddy current thickness gauge. Figure 4 shown.

[0067] The antibacterial experiment is to inoculate Staphylococcus aureus into a sterile liquid culture medium and culture it at 37°C for 24 hours. The concentration of the bacterial solution is measured by spectrophotometry and adjusted to 104CFU / mL. From the prepared bacterial suspension of Staphylococcus aureus, 200μL is taken and dripped on the surface of the micro-arc oxygen sample, and placed in a 37°C constant temperature incubator for moisturizing culture for 24 hours. After moisturizing culture, the bacterial solution on the surface of the sample is fully mixed and diluted 10 times in sequence (i.e. 1:10, 1:102, 1:103, 1:104, 1:105). At each dilution factor, 50μL of the bacterial suspension is taken and evenly dripped into a 9cm sterile culture dish in sequence, and the operation is repeated three times. After incubation at 37°C for another 12 hours, the colonies can be observed and counted. Finally, the antibacterial rate is calculated using formula (1):

[0068] F=(MN) / M×100% (1)

[0069] Wherein, F is the antibacterial rate (%), M is the number of bacterial colonies attached to the sample that has not been treated with micro-arc oxygen, and N is the number of bacterial colonies in the sample treated with micro-arc oxygen.

[0070] The corrosion voltage and corrosion current were measured by electrochemical testing on an electrochemical workstation (Autolab-PGSTAT302N, Metrohm, Switzerland, Europe) equipped with a standard three-electrode system, with a platinum electrode as the counter electrode, an Ag / AgCl electrode as the reference electrode, and the sample as the working electrode (exposed surface area of ​​1 cm 2 ). Before starting the polarization curve evaluation, the samples were immersed in a 3.5wt% NaCl electrolyte solution for 30 minutes to record the open circuit potential (OCP). After stabilization in 3.5wt% NaCl for 30 minutes, potentiodynamic polarization tests were performed from -0.2V to 0.1V relative to the open circuit potential (OCP) at a scan rate of 1mV / s. The corrosion current density (Icorr) and corrosion potential (Ecorr) were obtained using the Tafel extrapolation method.

[0071] Example 6

[0072] The difference between this embodiment and embodiment 5 is that the mass concentration of copper oxide nanoparticles is increased to 15 g / L, and other implementation conditions are the same.

[0073] The antibacterial rate of the micro-arc oxidation antibacterial and corrosion-resistant film prepared in this embodiment is 99.99% (Staphylococcus aureus), the corrosion voltage is +0.697V, and the corrosion current is 1.89×10 -7 The film thickness is 50μm to 60μm.

[0074] Example 7

[0075] The difference between this embodiment and embodiment 5 is that the forward voltage is 400V, and other implementation conditions are the same.

[0076] The antibacterial rate of the micro-arc oxidation antibacterial and corrosion-resistant film prepared in this embodiment is 89.69% (Staphylococcus aureus), the corrosion voltage is +0.297V, and the corrosion current is 3.89×10 -7 The film thickness is 35μm to 45μm.

[0077] Example 8

[0078] The difference between this embodiment and embodiment 5 is that the negative voltage is 70V, and other implementation conditions are the same.

[0079] The antibacterial rate of the micro-arc oxidation antibacterial and corrosion-resistant film prepared in this embodiment is 84.53% (Staphylococcus aureus), the corrosion voltage is +0.242V, and the corrosion current is 4.68×10 -7 The film thickness is 30μm to 40μm.

[0080] Example 9

[0081] The difference between this embodiment and embodiment 5 is that a unidirectional mode micro-arc oxidation treatment is adopted, the forward voltage is 600V, no negative voltage is applied, and other implementation conditions are the same.

[0082] The antibacterial rate of the micro-arc oxidation antibacterial and corrosion-resistant film prepared in this embodiment is 85.26%, the corrosion voltage is +0V, and the corrosion current is 9.51×10 -7 The film thickness is 10μm to 20μm.

[0083] Example 10

[0084] The difference between this embodiment and embodiment 5 is that no CuO nanoparticles are added to the working solution, and other implementation conditions are the same.

[0085] The antibacterial rate of the micro-arc oxidation antibacterial and corrosion-resistant film prepared in this embodiment is 45.36% (Staphylococcus aureus), the corrosion voltage is +0.103V, and the corrosion current is 7.53×10 -7 The film thickness is 30μm to 40μm.

[0086] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing an antibacterial and corrosion-resistant micro-arc oxidation film on an aluminum alloy surface, characterized in that: The method treats an aluminum alloy workpiece by micro-arc oxidation to form a film layer on the surface of the aluminum alloy; the electrolyte of the micro-arc oxidation comprises water, alkaline hydroxide, silicate, and nano CuO particles; in the electrolyte, the mass concentration of the alkaline hydroxide is 1g / L-15g / L, the mass concentration of the silicate is 1g / L-25g / L, and the mass concentration of the nano CuO particles is 0.1g / L-20g / L; The micro-arc oxidation uses an aluminum alloy workpiece as an anode and a stainless steel container as a cathode, and uses a pulsed AC power supply for treatment, with a forward voltage of 200V-700V, a negative voltage of 50-150V, a pulse width of 200ms-4000ms, an interval between pulses of 200ms-1000ms, a temperature of 20°C-85°C, and a treatment time of 2min-30min.

2. The preparation method according to claim 1, characterized in that: The forward voltage of the micro-arc oxidation discharge is 400V-600V, the negative voltage is 70V-120V, the pulse width is 1000ms-3000ms, and the pulse interval is 250ms-750ms; the hydroxide concentration is 1-3g / L, the silicate concentration is 2-5g / L, and the nano-CuO particle concentration is 8-15g / L.

3. The preparation method according to claim 1, characterized in that: The pH value of the electrolyte is 8-14.

4. The preparation method according to claim 1, characterized in that: The alkaline hydroxide includes one or more of potassium hydroxide and sodium hydroxide; the silicate includes one or more of sodium silicate and potassium silicate; the nano copper oxide particles have a diameter of 1nm-100nm, and preferably have a diameter of 40nm-60nm.

5. The preparation method according to claim 1, characterized in that: The electrolyte is stirred before micro-arc oxidation to form a colloid in which nano CuO particles are evenly dispersed.

6. The preparation method according to claim 1, characterized in that: The power supply is a bipolar pulse power supply, which adopts a unidirectional mode or a unidirectional first and then bidirectional working mode.

7. The preparation method according to claim 1, characterized in that: The aluminum alloy is 2024 aluminum alloy, 7075 aluminum alloy or 6061 aluminum alloy.

8. An antibacterial and corrosion-resistant micro-arc oxidation film on the surface of an aluminum alloy, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the antibacterial and corrosion-resistant micro-arc oxidation film on the surface of the aluminum alloy as claimed in claim 8 in the preparation of microsurgical instrument materials, orthopedic external fixator materials, and thoracic surgical instrument materials.

Citation Information

Patent Citations

  • Copper oxide / aluminum oxide composite catalyst and preparation method and special micro-arc oxidation electrolyte thereof

    CN103088387A

  • Preparation method of antibacterial wear-resistant coating on surface of titanium implant material

    CN112981493A